Agrarian Reform in Indonesia: Analyze Concepts and Their Implementation from a Governance Perspective - Hariadi Kartodiharjo; Eko Cahyonob (Jurnal Manajemen Hutan Tropika, 2021)
Analysis of the relationship between inequality, agrarian reform, and corruption as well as public administration reform has not been discussed, both in terms of the formation and implementation of agrarian reform in Indonesia. This article aims to explore the concept and implementation of agrarian reform, as well as the influence of governance conditions in the management of natural resources in the implementation of agrarian reform. With the characteristics of agrarian issues in Indonesia, land administration and those related to the implementation of redistribution of benefits from the use of natural resources need to be strengthened with appropriate concepts or theories, including public information disclosure as a fulfillment of substantive and deliberative implementation of democracy. In addition, by referring to experiences in other countries, agrarian reform needs to be carried out by reducing the level of clientelism and implemented through a number of corruption prevention and prosecution programs, especially in the fields of land and other natural resources.